(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Introduction: Post-Stroke Fatigue (PSF) is the most common debilitating and persistent symptom after a stroke. The impact of fatigue increases during the first year of post-stroke. When most of the recovery has taken place, fatigue could remain an important problem with disabling consequences for everyday life. Understanding the effect of PSF on cognition and mobility outcomes will help to better manage existing fatigue symptoms in stroke patients and develop strategies to optimize mobility and cognitive performance in patients with the chronic stage of stroke. With this background in mind, the present study aims at establishing a relationship between post-stroke fatigue and cognitive and motor performance among persons with stroke. Aim: To correlate fatigue with cognition and motor performance in stroke patients Materials and Method: This is the pilot study where 15 post-stroke patients fulfilling the inclusion and exclusion criteria were included by using the purposive sampling technique. Fatigue was assessed using Fatigue Scale for Motor and Cognitive Function. Motor Function was assessed by using Fugl Meyer Scale for upper and lower extremity, Chedokes Arm and Hand Inventory, Lower Extremity Functional Scale, and Berg Balance Scale. Cognition was assessed by using the Montreal Cognitive Assessment Scale. Using the scores of these scales, fatigue was correlated with motor and cognitive functions using Karl Pearson’s correlation test. Result: The study found a moderately significant correlation between Fatigue and Cognition (r=-0.605 p<0.05) and a highly significant correlation between fatigue and motor performance (r=-0.804 p<0.001). Conclusion: This study provides evidence that post-stroke fatigue has significant relationships with both motor performance and cognitive performance. It is important to consider the influence of fatigue when planning and delivering interventions for individuals with stroke.